(untitled) (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2021)
The main objective of this research is to identify and analyze the contribution of third party funds and the growth of financing in determining profitability in Islamic commercial banks in Indonesia for the period 2015-2019. Where profitability is the dependent variable and third party funds and financing growth is the independent variable. This Research type represent the quantitative research is comparability origin.. The data used in this study are secondary data, namely the financial statements of 6 Islamic public banks from the 2015 - 2019 period. The statistical method in this research is multiple linear regression analysis and correlation analysis using IBM SPSS Statistic 25.The results of this study indicate that simultaneously third party funds and financing growth have a significant effect on the profitability of Islamic Commercial Banks. As partially, the Current Party Fund has a significant effect on the profitability of Islamic Commercial Banks, and financing growth does not have a significant effect on the profitability of Islamic Commercial Banks.